2010
DOI: 10.1074/jbc.m110.147850
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-β-selective Ligands Alleviate High-fat Diet- and Ovariectomy-induced Obesity in Mice

Abstract: Obesity is an epidemic problem affecting millions of people in the Western hemisphere and costs the United States economy more than $200 billion annually. Currently, there are no effective treatments to combat obesity. Recent studies have implicated the constitutive activity of estrogen receptor (ER) ␤ as an important regulator of metabolic diseases. However, the potential of ER-␤-selective ligands to offset obesity is not clear. We evaluated the pharmacological effect of ER-␤-selective ligands (␤-LGNDs) in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
118
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 71 publications
8
118
0
2
Order By: Relevance
“…The results conclusively demonstrated that the effects were not due to the cross reactivity with ER-a, as evidenced by the lack of hypothalamus-pituitary-gonadal axis activation and uterine weight increase (Yepuru et al, 2010).…”
Section: Er-b Selective Ligands As Novel Therapeutics For Obesity Andsupporting
confidence: 56%
See 4 more Smart Citations
“…The results conclusively demonstrated that the effects were not due to the cross reactivity with ER-a, as evidenced by the lack of hypothalamus-pituitary-gonadal axis activation and uterine weight increase (Yepuru et al, 2010).…”
Section: Er-b Selective Ligands As Novel Therapeutics For Obesity Andsupporting
confidence: 56%
“…4) for 12 weeks. The body weights of mice fed with a high-fat diet and treated with an ER-b-selective agonist were significantly lower than those of vehicle-treated mice fed with a high-fat diet and were not different from the body weights of mice maintained on a normal diet (Yepuru et al, 2010). In addition to the body weight changes, we observed favorable changes in other biomarkers of metabolism, including cholesterol, leptin, and glucose tolerance.…”
Section: Er-b Selective Ligands As Novel Therapeutics For Obesity Andmentioning
confidence: 59%
See 3 more Smart Citations